Royalty Fee Bisnis Waralaba Ritel di Kota Makassar dalam Perspektif Hukum Ekonomi Syariah - Afifah, Andi Nur; Sohrah; Kara, Muslimin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2021)
The aim of this research was to determine and understand the royalty fees for retail store franchise business in the perspective of Islamic economic law in the city of Makassar. This research was a type of qualitative descriptive research (non-statistical) using normative, phenomenological, and sociological approaches. Findings of this research revealed that: First, the franchise of company X with its franchisee was in accordance with the Islamic law, there was no element of fraud in terms of contracts and agreements which was implemented in transparency. While, the franchise of company Y and its franchisee, there were different perceptions of policies related to the contract and franchise agreement, namely the absence of a written signing so that it was not in accordance with sharia, but both parties agreed on considerations and amendment policies that made specifically by the franchisee. Second, the implementation of royalty fees between the two companies had been carried out in transparency. The difference of both companies and their franchisees was from the policy of late payment of royalty fees. Company X and its franchisee used a maximum three-month deadline with an interest system, this was not adjusted to Islamic law because interest includes usury. Then, company Y and its franchisee would absolutely not use the delay system policy, because the royalty fee would automatically be deducted from the franchisee's cashback by purchasing products at Company Y.